Bronze Age worlds - Johnston, Robert, 1973- author.
1 online resource
Keywords: "Bronze Age Worlds brings a new way of thinking about kinship to the task of explaining the formation of social life in the Bronze Age Britain and Ireland. Britain and Ireland's diverse landscapes and societies experienced varied and profound transformations during the twenty-fifth to eighth centuries BC. People's lives were shaped by migrations, changing beliefs about death, making and thinking with metals, and living in houses and field systems. This book offers accounts of how these processes emerged from social life, from events, places and landscapes, informed by a novel theory of kinship. Kinship was a rich and inventive sphere of culture that incorporated biological relations but was not determined by them. Kinship formed personhood and collective belonging, and associated people with nonhuman beings, things and places. The differences in kinship and kinwork across Ireland and Britain brought textures to social life and the formation of Bronze Age worlds. Bronze Age Worlds offers new perspectives to anthropologists and archaeologists interested in the effects of kinship on Bronze Age societies and cultural development"--